Effects of the Oral Oxytocin Receptor Antagonist Tocolytic OBE001 on Reproduction in Rats. (April 2016) - Pohl, Oliver; Perks, Deborah; Rhodes, Jon; Comotto, Laura; Baldrick, Paul; Chollet, André
Background: OBE001 is a novel, orally active nonpeptide oxytocin receptor antagonist under development for the treatment of preterm labor and improvement in embryo implantation and pregnancy rate in assisted reproductive technology (ART). The reproductive safety of OBE001 was evaluated in customized fertility embryonic development (FER)/early embryonic development (EED) and fetal development (FD) and pre/postnatal development (PPN) studies mimicking clinical exposure scenarios. Methods: Oral OBE001 was evaluated at doses of 37.5, 75, and 125 mg/kg/d in female rats during a FER/EED study (from premating to implantation) and throughout FD during a FD/PPN study. Results: No OBE001 effects were observed during the FER/EED study. The FD/PPN study did not result in adverse OBE001 effects in females allowed to litter, their offspring, and second-generation fetuses. Females at 125 mg/kg/d who underwent cesarean section before term had slight reductions in body weights and food consumption, and associated fetuses had slightly delayed ossification of skull bones, which was not adverse in the absence of effects on live offspring. Conclusion: OBE001 at up to 125 mg/kg/d had no effects on EED and no adverse effects on FD and postnatal development of rats. These results constitute an important step toward the development of OBE001 in preterm labor and ART indications.